The Advancement of titles of stories in the stories published in “paiv” Magazine: (1993-2003) - Hemin Omar Ahmad; Gahin Nzar Ibrahim (QALAAI ZANIST JOURNAL, 2024)
The title is the doorstep to a literary text. Through the doorstep, it gives keys to the reader, a horizon for suggestions and opens ahead a positive or negative standard after motivating the reader to go into the meanings in the story. It is worth mentioning that the title is like a critical term that took its direction from the method of symbology for working on the text. The stories of “Paiv” magazine have been chosen for this research. Since 1993 it started to spread in the Bahdinan area and it still continues to spread. Thus, the hypothesis of this research is to seek for noticeable changes and progress in the titles of the stories that occurred in this period. Also, how the writers in the area dealt with producing the titles before the uprising and after the uprising and the major changes in quality and meaning.